Magnetic liquid for liquid medium sealing and preparation method thereof
By increasing the solid content and viscosity of magnetic liquid and doping with dysprosium ions ferrite nanomagnetic particles, the problems of low viscosity and poor anti-shrinkage in liquid medium sealing are solved, and efficient anti-shrinkage and self-repairing performance is achieved.
Patent Information
- Application Number
- CN202510012751.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-08
AI Technical Summary
The existing magnetic liquids for sealing liquids have low viscosity, low saturation magnetization and poor anti-shrinkage limit their application in liquid medium sealing.
By increasing the viscosity of the base carrier liquid and the solid content of the magnetic liquid, combined with ferrite nanomagnetic particles doped with dysprosium ions, the saturation magnetization and stability of the magnetic liquid are enhanced, thereby enhancing its anti-shrink performance and self-healing performance in a liquid medium sealing environment.
It realizes high viscosity and high saturation magnetization of magnetic liquids, improves its anti-shrink performance and self-repair performance in liquid medium sealing, and is suitable for applications in harsh environments.
Smart Images

Figure CN119786180A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic sealing material preparation, and in particular to a magnetic liquid used for liquid medium sealing and a preparation method thereof. Background Art
[0002] Magnetic liquid is a new type of functional material that has both the fluidity of liquid and the magnetism of solid magnetic materials. It is a stable colloidal liquid formed by dispersing nanomagnetic particles coated with surfactants into a base carrier liquid. When there is no external magnetic field, it behaves as a freely flowing Newtonian fluid. When a magnetic field is applied, the magnetic particles randomly distributed in the base carrier liquid will form a chain structure along the magnetic field, causing the viscosity of the magnetic liquid to increase sharply. Due to its excellent controllability, it is widely used in various harsh conditions in magnetic liquid sealing, shock absorption, medical equipment, sound adjustment and other fields.
[0003] Among them, magnetic liquid seal is a new type of fluid sealing technology that uses magnetic field control. Compared with other sealing forms, it has the advantages of zero leakage, long life, high reliability, ability to withstand high speed and low viscous friction. Therefore, it has broad development space and important application value in aerospace, mechanical engineering, precision instruments and other fields.
[0004] The failure mechanism of sealing when using magnetic liquid to seal liquid is more complicated than that of gas or vacuum. The reason is that the sealed liquid is in direct contact with the magnetic liquid, and the sealed liquid dissolves in the magnetic liquid, resulting in a decrease in sealing performance. In addition, the rotation of the shaft causes the magnetic liquid and the sealed liquid to move relative to each other, resulting in a speed difference at the contact interface between the two phases, and the instability at the contact surface between the two phases, causing part of the magnetic liquid to be centrifuged out, reducing the amount of magnetic liquid and reducing the sealing ability.
[0005] Patent CN202410070067.6 records a magnetic liquid and its preparation method, which uses a composite surfactant to coat nano-scale magnetic particles, and uses engine oil with a viscosity grade of LAN-32 or above as the base carrier liquid. The composite surfactant is composed of a mixture of long-chain fatty acids containing more than 20 carbon atoms and medium- and short-chain fatty acids containing less than 8 carbon atoms in a mass ratio of 1: (0.8-1.4). The magnetic liquid has a high viscosity and has the advantage of anti-scouring. However, the LAN-5 engine oil-based magnetic liquid used in the magnetic liquid has poor stability in high temperature environments and poor acid and alkali resistance. It cannot be used for sealing of special liquid media, such as the highly corrosive environment at sea when sealing the main shaft of a large ship.
[0006] Patent CN105469924B describes a method for preparing a fluoroether compound-based magnetic liquid, which prepares a fluoroether compound-based magnetic liquid with high stability by dissolving an active agent in a transition liquid and allowing the active agent to fully contact and adsorb nanoparticles to obtain particles with good coating effects. However, the fluoroether compound-based magnetic liquid in the preparation method has low viscosity and a low content of magnetic particles. If used in sealing applications of liquid media, it is easily washed away by the liquid medium, thereby causing sealing failure.
[0007] It can be seen that the existing magnetic liquids used for sealing liquids have the characteristics of low viscosity, low saturation magnetization intensity and poor anti-scouring, which greatly limit the use of magnetic liquids for sealing liquid media. Summary of the invention
[0008] Based on the low saturation magnetization intensity of the magnetic liquid currently prepared for sealing liquid, the problem of using the magnetic liquid for sealing liquid medium is greatly limited. The purpose of the present invention is to provide a magnetic liquid for sealing liquid medium and a preparation method thereof. By increasing the viscosity of the base carrier liquid and the solid content of the magnetic liquid, the saturation magnetization intensity and stability of the magnetic liquid are taken into account. At the same time, the higher solid content also effectively increases the viscosity of the magnetic liquid, thereby improving the anti-scouring performance and self-repairing performance of the magnetic liquid in the liquid medium sealing environment.
[0009] The present invention is achieved through the following technical solutions:
[0010] In a first aspect, the present application provides a magnetic liquid for sealing a liquid medium, comprising nano magnetic particles, a surfactant and a base carrier liquid;
[0011] The nano magnetic particles are coated by the surfactant and uniformly dispersed in the base carrier liquid;
[0012] Taking the total mass of the magnetic liquid as 100%, the mass fraction of the solid particles of the magnetic liquid is 60% to 70%, and the mass fraction of the base carrier liquid is 30% to 40%;
[0013] The base carrier fluid includes a highly hydrophobic oil base with high viscosity;
[0014] The nano magnetic particles include ferrite nano magnetic particles Dy doped with dysprosium ions. x Fe 3-x O4, where x represents the doping amount of dysprosium ions.
[0015] The saturation magnetization intensity of the nanomagnetic particles is 80-100emu / g.
[0016] The magnetic liquid is centrifuged to remove the cluster particles in the liquid, the centrifugal speed is 3000r / min, and the centrifugal time is 30min to 60min.
[0017] Ferrite nanoparticles usually have a spinel structure, and the molecular formula of Fe3O4 is (Fe 3+ ) A [Fe 2+ Fe 3+ ] B O4, for one "molecule", Fe 2+ Located in the octahedral gap formed by oxygen ions (B position), the ion magnetic moment is 4μ B , μ B is the Bohr magneton; two Fe 3+ They are located in the tetrahedron (A position) and the octahedral gap (B position), and the ionic magnetic moment is 5μ B , their antispins are parallel, and their magnetic moments cancel each other out. Theoretically, the magnetic moment of a molecule is μ = [4μ B +5μ B ]-5μ B =4μ B The ferrite nanoparticles in the magnetic liquid of the present invention are doped with rare earth element Dy 3+ , while Dy 3+ The saturation magnetization of the ferrite nanoparticles increases due to the preferential occupation of the B site. This is because the magnetic moment of the dysprosium ion is 7.92μ B , while the magnetic moment of iron ions is 5μ B , the appropriate amount of dysprosium ion doping can increase the magnetic moment at the B position, thereby improving the overall magnetic properties of the material.
[0018] The substance that provides magnetism in magnetic liquid is nanomagnetic particles. Under the same nanomagnetic particles, the more nanomagnetic particles contained in the magnetic liquid, the stronger the magnetic force provided under the magnetic field, thereby effectively improving the saturation magnetization intensity of the magnetic liquid. However, simply increasing the content of magnetic particles will reduce the sedimentation stability of the magnetic liquid, which is not conducive to practical engineering applications.
[0019] The present invention takes into account the saturation magnetization intensity and stability of the magnetic liquid by adjusting the content of the base carrier liquid and the solid particles, and at the same time improves the viscosity of the magnetic liquid, thereby improving the anti-scouring performance and self-repairing performance of the magnetic liquid in a liquid medium sealing environment.
[0020] As a preferred embodiment of the present application, the doping amount x of dysprosium ions is 0.05 to 0.10.
[0021] As a preferred embodiment of the present application, the base carrier fluid includes perfluoropolyether oil.
[0022] Among them, the molecular weight of perfluoropolyether oil is M w At least 7480 g / mol.
[0023] As a preferred embodiment of the present application, the surfactant includes perfluoropolyether carboxylic acid.
[0024] Among them, the molecular weight M of perfluoropolyether carboxylic acid w At least 5000 g / mol.
[0025] As a better implementation in the present application, the mass ratio of the nanomagnetic particles to the surfactant is 1:(0.5-0.8).
[0026] As a preferred embodiment of the present application, the magnetic liquid is subjected to a magnetic field-free state, a room temperature of 25°C, and a shear rate of 4.64s -1 The viscosity is 80Pa·s to 150Pa·s.
[0027] As a better implementation in the present application, the saturation magnetization intensity of the magnetic liquid is 25emu / g to 30emu / g.
[0028] As a better implementation in the present application, the magnetic liquid does not undergo stratification and sedimentation after centrifugation at 3000 r / min for 30 minutes.
[0029] In a second aspect, the present application provides a method for preparing a magnetic liquid for liquid medium sealing, comprising the following steps:
[0030] (1) stirring a mixed solution containing ferric ions, ferrous ions and dysprosium ions under heating conditions, adding sodium hydroxide to cause a coprecipitation reaction, and preparing nanomagnetic particles;
[0031] (2) adding dilute hydrochloric acid to the mixed solution to adjust the pH value of the mixed solution in step (1) to be weakly acidic, and adding a surfactant;
[0032] (3) separating the coated nanomagnetic particles in the mixed solution of step (2), and then washing them with ultrapure water for several times until the pH value of the supernatant of the mixed solution is neutral;
[0033] (4) separating the washed nano-magnetic particles from the mixed solution in step (3) and drying them;
[0034] (5) The nano-magnetic particles dried in step (4) are stirred and dispersed in a base carrier liquid to prepare a magnetic liquid.
[0035] The heating method in step (1) is water bath heating, and the heating temperature is controlled at 50°C to 70°C.
[0036] The drying method in step (4) is low-temperature drying under vacuum, wherein the temperature during drying is controlled at 50°C to 70°C.
[0037] As a preferred embodiment of the present application, the pH value of the mixed solution in step (2) is adjusted to 5-6.
[0038] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0039] (1) The magnetic liquid of the present invention is in the absence of a magnetic field, at room temperature (25°C), and at a shear rate of 4.64s -1 The viscosity is 80-150Pa·s. Such high viscosity makes the magnetic liquid have excellent anti-scouring and self-healing properties, making it more suitable for sealing liquid media.
[0040] (2) The nanomagnetic particles prepared in the present invention are ferrite nanomagnetic particles Dy doped with dysprosium ions. x Fe 3- x O4, whose saturation magnetization is at least 80emu / g, has excellent saturation magnetization and anti-oxidation properties;
[0041] (3) The saturation magnetization of the magnetic liquid prepared in the present invention is at least 25emu / g, which meets the actual requirements for liquid medium sealing;
[0042] (4) The magnetic liquid for liquid medium sealing prepared in the present invention has a simple preparation process, a safe process, easy-to-obtain materials, and low requirements on equipment, and is suitable for large-scale promotion;
[0043] (5) The magnetic liquid prepared in the present invention did not undergo stratification and sedimentation after centrifugation at 3000 r / min for 30 min, and was able to maintain a high dispersion stability during sealing applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0045] Figure 1 is a VSM curve diagram of the dysprosium-doped ferrite nanomagnetic particles prepared in Example 1 of the present invention;
[0046] Figure 2 is a viscosity curve of the magnetic liquid prepared in Example 1 of the present invention;
[0047] Figure 3 is a VSM curve diagram of the magnetic liquid prepared in Example 1 of the present invention;
[0048] Figure 4 is a VSM curve diagram of the dysprosium-doped ferrite nanomagnetic particles prepared in Example 2 of the present invention;
[0049] Figure 5 is a viscosity curve of the magnetic liquid prepared in Example 2 of the present invention;
[0050] Figure 6 is a VSM curve diagram of the magnetic liquid prepared in Example 2 of the present invention;
[0051] Figure 7 The VSM curve of the ferrite nano-magnetic particles prepared in Comparative Example 1 of the present invention;
[0052] Figure 8 is a viscosity curve of the magnetic liquid prepared in Comparative Example 1 of the present invention;
[0053] Fig. 9 This is a VSM curve diagram of the magnetic liquid prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0055] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] This embodiment provides a method for preparing a magnetic liquid for liquid medium sealing, and the specific steps are as follows:
[0058] S1. 40.58 g of FeCl3·6H2O, 27.8 g of FeSO4·7H2O and 2.32 g of DyCl3 were added to 500 ml of water to dissolve to form a mixed solution; 30 g of NaOH powder was stirred and dissolved in 10 ml of water to obtain a NaOH solution; then a mixed solution containing ferric ions, ferrous ions and dysprosium ions was added to the NaOH solution to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution was 11, the reaction temperature was 60°C, the reaction time was 40 minutes, and the reaction process was mechanically stirred at a stirring rate of 400 rpm to generate dysprosium-doped ferrite nanoparticles (Dy 0.1 Fe 2.9 O4). Figure 1 As shown, the saturation magnetization intensity of the ferrite nanoparticles is 88.35emu / g, the coercive force is very small, and the magnetization curve is "S" shaped. The particles have the characteristics of superparamagnetic materials.
[0059] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid to coat dysprosium-doped ferrite nanomagnetic particles, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, and the mass ratio of the perfluoropolyether carboxylic acid to the dysprosium-doped ferrite nanomagnetic particles is 1:2. The temperature of the coating process is 60° C. and the time is 120 minutes. The coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain dysprosium-doped ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0060] S3. Separate the coated dysprosium-doped ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash the mixed solution with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0061] S4, vacuum drying the cleaned coated dysprosium-doped ferrite nanoparticles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0062] S5, dispersing the coated dysprosium-doped ferrite nanoparticles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 7480g / mol to obtain a magnetic liquid. The mass fraction of the coated dysprosium-doped ferrite nanoparticles is 60%, and the mass fraction of the perfluoropolyether oil-based liquid is 40%. A mechanical stirring method is adopted, the stirring speed is 1000r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000r / min, and the centrifugal time is 30min.
[0063] The magnetic liquid prepared by the method of Example 1 was subjected to the following performance tests:
[0064] 1. Use the Physica MCR 301 rheometer produced by Anton Paar to characterize the rheological properties of the base magnetic fluid. Use the MRD magnetorheological device, flat plate and PP20 rotor for measurement. Place a certain amount of magnetic fluid on the flat plate, adjust the plate spacing to 0.05mm, and measure the viscosity, shear stress and other parameters of the magnetic fluid under different conditions. The test conditions are: different magnetic field strengths (0mT, 40mT, 100mT fixed magnetic field), room temperature, different shear rates (0.01~100s -1 Continuously changing).
[0065] like Figure 2As shown in the figure, with the increase of shear rate, the viscosity of magnetic fluid in the presence or absence of magnetic field shows a downward trend. This is because under the shear action, the microstructure in the magnetic fluid is orderly arranged along the shear surface. The viscosity of magnetic fluid increases with the increase of magnetic field strength. At a high shear rate of 10 2 s -1 When the magnetic fluid is heated to 20 ℃, the viscosity of the magnetic fluid is close to 100 Pa·s, which is a relatively high value.
[0066] 2. The Vibration Sample Magnetometer (VSM) model Lake Shore 7410 is used to characterize the hysteresis loop of the magnetic fluid, and its saturation magnetization, coercive force and other parameters can be obtained. The sensitivity of the device is 5×10 -7 emu, the maximum room temperature magnetic field reaches 2.88 T. The test conditions are: 25℃, magnetic field strength -25000~25000Oe.
[0067] like Figure 3 As shown, the saturation magnetization intensity of the magnetic liquid prepared after the nanomagnetic particles are dispersed is 26.97emu / g, the coercive force is very small, and the magnetization curve is "S" shaped. The magnetic liquid has the characteristics of superparamagnetic materials.
[0068] Example 2
[0069] This embodiment provides a method for preparing a magnetic liquid for liquid medium sealing. Different from Embodiment 1, in step S1 of this embodiment, the concentration ratio of iron ions to dysprosium ions is 20:1. The specific steps are as follows:
[0070] S1. 20.29g of FeCl3·6H2O, 13.9g of FeSO4·7H2O and 1.14g of DyCl3 were added to 500ml of water to dissolve to form a mixed solution; 30g of NaOH powder was stirred and dissolved in 10ml of water to obtain a NaOH solution; then a mixed solution containing ferric ions, ferrous ions and dysprosium ions was added to the NaOH solution to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution was 11, the reaction temperature was 60°C, the reaction time was 40 minutes, and the reaction process was mechanically stirred at a stirring rate of 400rpm to generate dysprosium-doped ferrite nanoparticles (Dy 0.05 Fe 2.95 O4). Figure 4 As shown, the saturation magnetization intensity of the ferrite nanoparticles is 92.77emu / g, the coercive force is very small, and the magnetization curve is "S" shaped. The particles have the characteristics of superparamagnetic materials.
[0071] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid to coat dysprosium-doped ferrite nanomagnetic particles, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, and the mass ratio of the perfluoropolyether carboxylic acid to the dysprosium-doped ferrite nanomagnetic particles is 1:2. The temperature of the coating process is 60° C. and the time is 120 minutes. The coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain dysprosium-doped ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0072] S3. Separate the coated dysprosium-doped ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash the mixed solution with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0073] S4, vacuum drying the cleaned coated dysprosium-doped ferrite nanoparticles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0074] S5, dispersing the coated dysprosium-doped ferrite nanoparticles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 7480g / mol to obtain a magnetic liquid. The mass fraction of the coated dysprosium-doped ferrite nanoparticles is 60%, and the mass fraction of the perfluoropolyether oil-based liquid is 40%. A mechanical stirring method is adopted, the stirring speed is 1000r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000r / min, and the centrifugal time is 30min.
[0075] The magnetic liquid prepared by the method of Example 2 was tested for the following properties:
[0076] 1. Use the Physica MCR 301 rheometer produced by Anton Paar to characterize the rheological properties of the base magnetic fluid. Use the MRD magnetorheological device, flat plate and PP20 rotor for measurement. Place a certain amount of magnetic fluid on the flat plate, adjust the plate spacing to 0.05mm, and measure the viscosity, shear stress and other parameters of the magnetic fluid under different conditions. The test conditions are: different magnetic field strengths (0mT, 40mT, 100mT fixed magnetic field), room temperature, different shear rates (0.01~100s -1 Continuously changing).
[0077] like Figure 5 As shown in the figure, with the increase of shear rate, the viscosity of magnetic fluid in the presence or absence of magnetic field shows a downward trend. This is because under the shear action, the microstructure in the magnetic fluid is orderly arranged along the shear surface. The viscosity of magnetic fluid increases with the increase of magnetic field strength. At a high shear rate of 102 s -1 When the magnetic fluid is heated to 20 ℃, the viscosity of the magnetic fluid is close to 100 Pa·s, which is a relatively high value.
[0078] 2. The Vibration Sample Magnetometer (VSM) model Lake Shore 7410 is used to characterize the hysteresis loop of the magnetic fluid, and its saturation magnetization, coercive force and other parameters can be obtained. The sensitivity of the device is 5×10 -7 emu, the maximum room temperature magnetic field reaches 2.88 T. The test conditions are: 25℃, magnetic field strength -25000~25000Oe.
[0079] like Figure 6 As shown, the saturation magnetization intensity of the magnetic liquid is 28.24emu / g, the coercive force is very small, the magnetization curve is "S" shaped, and the particles have the characteristics of superparamagnetic materials.
[0080] Example 3
[0081] This embodiment provides a method for preparing a magnetic liquid for sealing a liquid medium. The difference from Embodiment 2 is that the mass fraction of the coated dysprosium-doped ferrite nanomagnetic particles in step S5 of this embodiment is 70%. The specific steps are:
[0082] S1. 40.58 g of FeCl3·6H2O, 27.8 g of FeSO4·7H2O and 1.14 g of DyCl3 were added to 500 ml of water to dissolve to form a mixed solution; 30 g of NaOH powder was stirred and dissolved in 10 ml of water to obtain a NaOH solution; then a mixed solution containing ferric ions, ferrous ions and dysprosium ions was added to the NaOH solution to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution was 11, the reaction temperature was 60°C, the reaction time was 40 minutes, and the reaction process was mechanically stirred at a stirring rate of 400 rpm to generate dysprosium-doped ferrite nanoparticles (Dy 0.05 Fe 2.95 O4).
[0083] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid to coat dysprosium-doped ferrite nanomagnetic particles, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, and the mass ratio of the perfluoropolyether carboxylic acid to the dysprosium-doped ferrite nanomagnetic particles is 1:2. The temperature of the coating process is 60° C. and the time is 120 minutes. The coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain dysprosium-doped ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0084] S3. Separate the coated dysprosium-doped ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash the mixed solution with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0085] S4, vacuum drying the cleaned coated dysprosium-doped ferrite nanoparticles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0086] S5, dispersing the coated dysprosium-doped ferrite nanoparticles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 7480g / mol to obtain a magnetic liquid. The mass fraction of the coated dysprosium-doped ferrite nanoparticles is 70%, and the mass fraction of the perfluoropolyether oil-based liquid is 30%. A mechanical stirring method is adopted, the stirring rate is 1000r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000r / min, and the centrifugal time is 30min.
[0087] At high shear rates of 10 2 s -1 When the magnetic fluid is heated to 20 ℃, the viscosity of the magnetic fluid is close to 100 Pa·s, which is a relatively high value.
[0088] The saturation magnetization of the magnetic liquid is 25.95emu / g, which is a relatively high value.
[0089] Example 4
[0090] This embodiment provides a method for preparing a magnetic liquid for liquid medium sealing. Different from Embodiment 3, the molecular weight of the perfluoropolyether oil-based liquid used in step S5 of this embodiment is 11000 g / mol. The specific steps are as follows:
[0091] S1. 40.58g of FeCl3·6H2O, 27.8g of FeSO4·7H2O and 1.14g of DyCl3 were added to 500ml of water to dissolve to form a mixed solution; 30g of NaOH powder was stirred and dissolved in 10ml of water to obtain a NaOH solution; then a mixed solution containing ferric ions, ferrous ions and dysprosium ions was added to a sodium hydroxide solution to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution was 11, the reaction temperature was 60°C, the reaction time was 40 minutes, and the reaction process was mechanically stirred at a stirring rate of 400rpm to generate dysprosium-doped ferrite nanoparticles (Dy 0.05 Fe 2.95 O4).
[0092] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid to coat dysprosium-doped ferrite nanomagnetic particles, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, and the mass ratio of the perfluoropolyether carboxylic acid to the dysprosium-doped ferrite nanomagnetic particles is 1:2. The temperature of the coating process is 60° C. and the time is 120 minutes. The coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain dysprosium-doped ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0093] S3. Separate the coated dysprosium-doped ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash the mixed solution with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0094] S4, vacuum drying the cleaned coated dysprosium-doped ferrite nanoparticles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0095] S5, dispersing the coated dysprosium-doped ferrite nanoparticles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 11000 g / mol to obtain a magnetic liquid. The mass fraction of the coated dysprosium-doped ferrite nanoparticles is 70%, and the mass fraction of the perfluoropolyether oil-based liquid is 30%. A mechanical stirring method is adopted, the stirring rate is 1000 r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000 r / min, and the centrifugal time is 30 minutes.
[0096] At high shear rates of 10 2 s -1 When the magnetic fluid is heated to 20 ℃, the viscosity of the magnetic fluid is close to 100 Pa·s, which is a relatively high value.
[0097] The saturation magnetization of the magnetic liquid is 26.91emu / g, which is a relatively high value.
[0098] Comparative Example 1
[0099] This comparative example provides a method for preparing a magnetic liquid. Different from Example 1, the doping of dysprosium ions is omitted in step S1.
[0100] The specific steps are:
[0101] S1. Add 40.58gFeCl3·6H2O and 27.8gFeSO4·7H2O into 500ml water to dissolve and form a mixed solution; stir and dissolve 30gNaOH powder in 10ml water to obtain a NaOH solution; then add the mixed solution containing ferric ions and ferrous ions into a sodium hydroxide solution to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution is 11, the reaction temperature is 60°C, the reaction time is 40 minutes, and the reaction process is mechanically stirred at a stirring rate of 400rpm to generate ferrite nanomagnetic particles. Figure 7 As shown, the saturation magnetization intensity of the ferrite nanoparticles is 68.11emu / g, the coercive force is very small, and the magnetization curve is "S" shaped. The particles have the characteristics of superparamagnetic materials.
[0102] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid-coated ferrite nanomagnetic particles thereto, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, wherein the mass ratio of the perfluoropolyether carboxylic acid to the ferrite nanomagnetic particles is 1:2, the temperature of the coating process is 60° C., and the time is 120 minutes; the coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0103] S3. Separate the coated ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash them with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0104] S4, vacuum drying the cleaned coated ferrite nano magnetic particles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0105] S5, dispersing the coated ferrite nano magnetic particles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 7480g / mol to obtain a magnetic liquid. The mass fraction of the coated ferrite nano magnetic particles is 60%, and the mass fraction of the perfluoropolyether oil-based liquid is 40%. A mechanical stirring method is adopted, the stirring speed is 1000r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000r / min, and the centrifugal time is 30min.
[0106] The magnetic liquid prepared by the method of Comparative Example 1 was subjected to the following performance tests:
[0107] 1. Use the Physica MCR 301 rheometer produced by Anton Paar to characterize the rheological properties of the base magnetic fluid. Use the MRD magnetorheological device, flat plate and PP20 rotor for measurement. Place a certain amount of magnetic fluid on the flat plate, adjust the plate spacing to 0.05mm, and measure the viscosity, shear stress and other parameters of the magnetic fluid under different conditions. The test conditions are: different magnetic field strengths (0mT, 40mT, 100mT fixed magnetic field), room temperature, different shear rates (0.01~100s -1 Continuously changing).
[0108] like Figure 8 As shown in the figure, as the shear rate increases, the viscosity of the magnetic liquid in the presence or absence of a magnetic field shows a downward trend. This is because under the shearing action, the microstructure in the magnetic liquid is orderly arranged along the shearing surface. The viscosity of the magnetic liquid increases with the increase of the magnetic field strength. In addition, at the same shear rate and magnetic field, the viscosity of the magnetic liquid is less than the data in Examples 1 and 2. 2 s -1 At high shear rates, the viscosity of magnetic fluid is about 10 Pa·s.
[0109] 2. The Vibration Sample Magnetometer (VSM) model Lake Shore 7410 is used to characterize the hysteresis loop of the magnetic fluid, and its saturation magnetization, coercive force and other parameters can be obtained. The sensitivity of the device is 5×10 -7 emu, the maximum room temperature magnetic field reaches 2.88 T. The test conditions are: 25℃, magnetic field strength -25000~25000Oe.
[0110] like Fig. 9 As shown in the figure, the saturation magnetization of the magnetic liquid prepared after the nanomagnetic particles are dispersed is 14.54emu / g, which is significantly lower than the saturation magnetization value of the magnetic liquid in the embodiment. The coercive force is very small, and the magnetization curve is "S" shaped. The magnetic liquid has the characteristics of superparamagnetic materials. 3+ , the saturation magnetization of the prepared ferrite nanoparticles is low.
[0111] Comparative Example 2
[0112] This comparative example provides a method for preparing a magnetic liquid. Different from Example 1, this comparative example uses a small molecular weight (M w =920g / mol) perfluoropolyether oil-based carrier liquid to prepare magnetic liquid. The specific method is:
[0113] S1. 40.58g of FeCl3·6H2O, 27.8g of FeSO4·7H2O and 2.32g of DyCl3 were added to 500ml of water to dissolve to form a mixed solution; 30g of NaOH powder was stirred and dissolved in 10ml of water to obtain a NaOH solution; then sodium hydroxide solution was added to the mixed solution containing ferric ions, ferrous ions and dysprosium ions to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution was 11, the reaction temperature was 60°C, the reaction time was 40 minutes, and the reaction process was mechanically stirred at a stirring rate of 400rpm to generate dysprosium-doped ferrite nanoparticles (Dy 0.1 Fe 2.9 O4).
[0114] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid to coat dysprosium-doped ferrite nanomagnetic particles, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, and the mass ratio of the perfluoropolyether carboxylic acid to the dysprosium-doped ferrite nanomagnetic particles is 1:2. The temperature of the coating process is 60° C. and the time is 120 minutes. The coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain dysprosium-doped ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0115] S3. Separate the coated dysprosium-doped ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash the mixed solution with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0116] S4, vacuum drying the cleaned coated dysprosium-doped ferrite nanoparticles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0117] S5, dispersing the coated dysprosium-doped ferrite nanoparticles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 7480g / mol to obtain a magnetic liquid. The mass fraction of the coated dysprosium-doped ferrite nanoparticles is 60%, and the mass fraction of the perfluoropolyether oil-based liquid is 40%. A mechanical stirring method is adopted, the stirring speed is 1000r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000r / min, and the centrifugal time is 30min.
[0118] At high shear rates of 10 2 s -1 When the magnetic liquid is heated to 40 ℃, the viscosity of the magnetic liquid is close to 10 Pa·s, which is lower than the value in the embodiment. This is because the viscosity of the fluoroether oil selected for the magnetic liquid is relatively low (the smaller the molecular weight, the lower the viscosity).
[0119] Comparative Example 3
[0120] This comparative example provides a method for preparing a magnetic liquid. The difference from Example 1 is that the mass fraction of the coated dysprosium-doped ferrite nanomagnetic particles used in step S5 is 50%, and the mass fraction of the perfluoropolyether oil-based liquid is 50%. The specific steps are:
[0121] S1. 40.58g of FeCl3·6H2O, 27.8g of FeSO4·7H2O and 2.32g of DyCl3 were added to 500ml of water to dissolve to form a mixed solution; 30g of NaOH powder was stirred and dissolved in 10ml of water to obtain a NaOH solution; then sodium hydroxide solution was added to the mixed solution containing ferric ions, ferrous ions and dysprosium ions to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution was 11, the reaction temperature was 60°C, the reaction time was 40 minutes, and the reaction process was mechanically stirred at a stirring rate of 400rpm to generate dysprosium-doped ferrite nanoparticles (Dy 0.1 Fe 2.9 O4).
[0122] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid to coat dysprosium-doped ferrite nanomagnetic particles, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, and the mass ratio of the perfluoropolyether carboxylic acid to the dysprosium-doped ferrite nanomagnetic particles is 1:2. The temperature of the coating process is 60° C. and the time is 120 minutes. The coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain dysprosium-doped ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0123] S3. Separate the coated dysprosium-doped ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash the mixed solution with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0124] S4, vacuum drying the cleaned coated dysprosium-doped ferrite nanoparticles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0125] S5, dispersing the coated dysprosium-doped ferrite nanoparticles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 7480g / mol to obtain a magnetic liquid. The mass fraction of the coated dysprosium-doped ferrite nanoparticles is 50%, and the mass fraction of the perfluoropolyether oil-based liquid is 50%. A mechanical stirring method is adopted, the stirring speed is 1000r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000r / min, and the centrifugal time is 30min.
[0126] At high shear rates of 10 2 s -1When , the viscosity of the magnetic liquid is close to 10 Pa·s, which is lower than the value in the embodiment.
[0127] The saturation magnetization of the magnetic liquid was 20.59 emu / g, which was lower than the value in the example.
[0128] This is because the particle concentration in the magnetic liquid is lower than 60wt% and 70wt% in the examples, and as the particle concentration increases, the saturation magnetization of the magnetic liquid gradually increases, resulting in the saturation magnetization and viscosity of the magnetic liquid in the comparative example being lower than those in the examples.
[0129] Comparative Example 4
[0130] This comparative example provides a method for preparing a magnetic liquid. Different from Example 1, this comparative example uses a small molecular weight (M w =920g / mol) of perfluoropolyether carboxylic acid coated with dysprosium-doped ferrite nanoparticles. The specific method is:
[0131] S1. 40.58g of FeCl3·6H2O, 27.8g of FeSO4·7H2O and 2.32g of DyCl3 were added to 500ml of water to dissolve to form a mixed solution; 30g of NaOH powder was stirred and dissolved in 10ml of water to obtain a NaOH solution; then sodium hydroxide solution was added to the mixed solution containing ferric ions, ferrous ions and dysprosium ions to cause a coprecipitation reaction. The pH value of the coprecipitation reaction solution was 11, the reaction temperature was 60°C, the reaction time was 40 minutes, and the reaction process was mechanically stirred at a stirring rate of 400rpm to generate dysprosium-doped ferrite nanoparticles (Dy 0.1 Fe 2.9 O4).
[0132] S2. Adjust the pH of the reaction solution in step S1 to 6, and then add perfluoropolyether carboxylic acid to coat dysprosium-doped ferrite nanomagnetic particles, wherein the molecular weight of the perfluoropolyether carboxylic acid is 5000 g / mol, and the mass ratio of the perfluoropolyether carboxylic acid to the dysprosium-doped ferrite nanomagnetic particles is 1:2. The temperature of the coating process is 60° C. and the time is 120 minutes. The coating process adopts mechanical stirring at a stirring rate of 400 rpm to obtain dysprosium-doped ferrite nanomagnetic particles coated with perfluoropolyether carboxylic acid.
[0133] S3. Separate the coated dysprosium-doped ferrite nanoparticles from the mixed solution prepared in step S2 by magnetic attraction, and then wash the mixed solution with ultrapure water until the pH value of the washing solution is neutral, and wash 10 times.
[0134] S4, vacuum drying the cleaned coated dysprosium-doped ferrite nanoparticles, wherein the drying temperature is 70° C. and the drying time is 18 hours.
[0135] S5, dispersing the coated dysprosium-doped ferrite nanoparticles dried in step S4 in a perfluoropolyether oil-based liquid with a molecular weight of 7480g / mol to obtain a magnetic liquid. The mass fraction of the coated dysprosium-doped ferrite nanoparticles is 60%, and the mass fraction of the perfluoropolyether oil-based liquid is 40%. A mechanical stirring method is adopted, the stirring speed is 1000r / min, and the dispersion time is 72 hours. Finally, a centrifugal method is adopted to remove the cluster particles in the magnetic liquid, the centrifugal speed is 2000r / min, and the centrifugal time is 30min.
[0136] At high shear rates of 10 2 s -1 When , the viscosity of the magnetic liquid is close to 10 Pa·s, which is lower than the value in the embodiment.
[0137] The saturation magnetization of the magnetic liquid was 16.22 emu / g, which was lower than the value in the example.
[0138] This is because the surfactant used has a small molecular weight and cannot disperse the nano-magnetic particles well, causing some of the nano-magnetic particles to settle, which in turn leads to a low viscosity of the magnetic liquid.
[0139] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A magnetic liquid for sealing a liquid medium, characterized in that: It includes nano magnetic particles, surfactants and base carrier liquid; The nano magnetic particles are coated by the surfactant and uniformly dispersed in the base carrier liquid; Taking the total mass of the magnetic liquid as 100%, the mass fraction of the solid particles of the magnetic liquid is 60% to 70%, and the mass fraction of the base carrier liquid is 30% to 40%; The base carrier fluid includes a highly hydrophobic oil base with high viscosity; The nano magnetic particles include ferrite nano magnetic particles Dy doped with dysprosium ions. x Fe 3-x O4, where x represents the doping amount of dysprosium ions.
2. A magnetic liquid for sealing a liquid medium according to claim 1, characterized in that: The doping amount x of dysprosium ions is 0.05 to 0.
10.
3. The magnetic liquid for sealing a liquid medium according to claim 1, characterized in that: The base carrier liquid includes perfluoropolyether oil, the molecular weight of the perfluoropolyether oil is w At least 7480 g / mol.
4. The magnetic liquid for sealing a liquid medium according to claim 1, characterized in that: The surfactant comprises perfluoropolyether carboxylic acid, the molecular weight M of the perfluoropolyether carboxylic acid is w At least 5000 g / mol.
5. The magnetic liquid for sealing a liquid medium according to claim 1, characterized in that: The mass ratio of the nano magnetic particles to the surfactant is 1:(0.5-0.8).
6. A magnetic liquid for sealing a liquid medium according to any one of claims 1 to 5, characterized in that: The magnetic liquid is in the absence of a magnetic field, at room temperature of 25°C, and at a shear rate of 4.64s -1 The viscosity is 80Pa·s to 150Pa·s.
7. A magnetic liquid for sealing a liquid medium according to any one of claims 1 to 5, characterized in that: The saturation magnetization intensity of the magnetic liquid is 25emu / g to 30emu / g.
8. A magnetic liquid for sealing a liquid medium according to any one of claims 1 to 5, characterized in that: The magnetic liquid does not undergo stratification and sedimentation after centrifugation at 3000 r / min for 30 to 60 minutes.
9. A method for preparing a magnetic liquid for sealing a liquid medium, characterized in that: The following steps are involved: (1) stirring a mixed solution containing ferric ions, ferrous ions and dysprosium ions under heating conditions, adding sodium hydroxide to cause a coprecipitation reaction, and preparing nanomagnetic particles; (2) adding dilute hydrochloric acid to the mixed solution to adjust the pH value of the mixed solution in step (1) to be weakly acidic, and adding a surfactant; (3) separating the coated nanomagnetic particles in the mixed solution of step (2), and then washing them with ultrapure water for several times until the pH value of the supernatant of the mixed solution is neutral; (4) separating the washed nano-magnetic particles from the mixed solution in step (3) and drying them; (5) The nano-magnetic particles dried in step (4) are stirred and dispersed in a base carrier liquid to prepare a magnetic liquid.
10. The method for preparing a magnetic liquid for liquid medium sealing according to claim 9, characterized in that: The pH value of the mixed solution in step (2) is adjusted to 5-6.
Citation Information
Patent Citations
A kind of preparation method of fluoroether compound-based magnetic liquid
CN105469924B
Magnetic liquid and preparation method thereof
CN118116685A